Eexpress method of threshold voltage control of DMOS transistors in the process of their manufacturing - Politansky, Leonid; Lesinsky, Valentin (Видавництво Львівської політехніки, 2012)
There is shown the use of test structure for DMOS-structure threshold voltage control and correction.
Keywords: DMOS transistors; threshold voltage